Children’s rights and personal data protection in the jurisprudence of the European Court of Human Rights - Ruiz Díaz Arce, Sergio Daniel (2023)
This article analyses the jurisprudence of the European Court of Human Rights (ECtHR) in order to identify and characterise the argumentative conclusions produced by the Court in their decisions on personal data protection and that affect children’s rights. The data collection technique consisted of a search and selection of the arguments in the Court’s judgments on situations that refer to violations of personal data. For the argumentative analysis, through an argumentation scheme, a judgment of a case that refers to child protection against sexual online exploitation was selected. In this context, we have observed that the Court structured its arguments to verify the violation of privacy and protection of personal data using the following topics: (i) respect for private life; (ii) criminal-law provisions; and (iii) positive obligations. The use of these topics in the subsequent judgments of the ECtHR is also identified through the citations to justify their own decisions.